Perspektif Etika Bisnis Islam Terhadap Manajemen Laba - Nurliza Lubis; Nurul Hayati Panjaitan; Haiqal Alif Ramadhani; Fahriani Astuti Sitepu (Mumtaz: Jurnal Ekonomi dan Bisnis Islam, 2024)
This study's definition of earnings management is based on Schipper's view that earnings management is "managed engineering" by management to deliberately intervene in the process of determining earnings or financial reporting by utilizing accounting methods and policies for specific purposes. The purpose of this study is to investigate the earnings management practices from the point of view of Islamic business ethics. This study employs interviews, descriptive qualitative methods, techniques for data collection, and literature reviews. The study's findings demonstrate that Islamic business ethics do not apply to earnings management. The principles of monotheism and unity are embedded in Islamic business ethics. equal, balanced; freedom; responsibility; kindness, charity